DEVELOPMENT OF SMART BOX MEDIA IN SCIENCE LEARNING TO INCREASE INTEREST IN LEARNING IN CLASS IV PRIMARY SCHOOL STUDENTS - Harahap, Ali Badri; Darwis, Umar (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
This research is a type of research and development referring to the ADDIE model consisting of five development stages, namely analysis, design, development, implementation and evaluation. This research produces a product in the form of smart box media for science and science learning metamorphosis material in fourth grade elementary school. The instrument used to collect data was a questionnaire. The data analysis technique is descriptive qualitative. The results of the validation of the material expert's assessment received a score of 80% from 10 statements. The smart box media for science and science learning that has been developed is very valid and can be applied as a medium for the teaching and learning process in schools. The media expert validation results obtained a percentage of 96%. Based on the validation results of the smart box media in the science and science learning that was developed, it was found that the learning media that was developed was declared very valid or had a very good degree of validity. The validation results of three aspects were assessed, namely 1) attractiveness of color, 2) clarity of letters and language used and 3) quality of design. This percentage includes the criteria of "very suitable" to be used as a medium in learning activities for fourth grade elementary school students regarding imperfect metamorphosis. Overall, the assessment of the student response questionnaire scores that were reviewed by the teacher during the field trial amounted to 48 scores obtained from a maximum score of 50. This resulted in a percentage score of 96% which was categorized as very decent/good. The results of interviews with class IV students can be concluded from a total of 15 students. 12 students stated learning